Identifikasi Bakat dan latihan Konsentrasi Siswa SD 010 Desa Batusasak - Alficandra, Alficandra; Makorohim, M. Fransazeli; Yani, Ahmad; Zulkifli, Zulkifli; Henjilito, Raffly; Ruzain, Raihanatu Binqalbi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The problems faced are related to the sports achievement coaching program in the Kampar Regency Youth and Sports Office, Riau Province. The coaching carried out certainly requires a lot of input and reinforcement in the field of achievement coaching. One of the supporting factors needed here is Talent Identification in early childhood. Talent is an advantage in the form of an ability possessed by a person in a field, where with his talent he does not have to study and practice hard in that field like other people who do not have talents like him. In addition, talent is carried by a person since birth and is only known as he grows older so that talent identification is needed. The activities of strengthening the concept of talent identification are carried out in several stages. First, the preparation stage, namely conducting surveys and discussions to obtain the information needed, setting targets, preparing materials and other needs. Second, the implementation stage with activities to conduct pre-tests and deliver material on concentration training and talent identification. Third, the evaluation stage by conducting post-tests and analyzing the final results of the Community Service activities that have been carried out. This community service activity went well from the beginning to the end of the activity, participants participated enthusiastically and actively in discussing with the speakers. The final result obtained was an increase in participant understanding related to the application of the concept of student talent identification in improving athlete achievement.